2019
DOI: 10.1037/npe0000104
|View full text |Cite
|
Sign up to set email alerts
|

Inferiority, not similarity of the decoy to target, is what drives the transfer of attention underlying the attraction effect: Evidence from an eye-tracking study with real choices.

Abstract: Recent studies reported that the attraction effect, whereby inferior decoys cause choice reversals, fails to replicate if the choice options are presented in a pictorial rather than abstract numerical form. We argue that the pictorial setting makes the similarity between decoy and target salient, while the abstract one emphasizes the inferiority relationship between them, crucial for the effect to occur. Thus, we used a novel experimental design in which both similarity and inferiority are equally easy to judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…This is the reason why the revisits of the decoy delay attribute were never associated with subjects' preferences, but only the decoy amount revisits revealed the comparative advantage of choosing the target option, pushing subjects to shift their preferences towards it. This pattern is also consistent with the Król & Król (2019) results, in which only the revisits for the attribute that highlighted the inferiority of the decoy pushed subjects to prefer the target option.…”
Section: Fixation Dynamic Plot In Td Blocksupporting
confidence: 89%
See 1 more Smart Citation
“…This is the reason why the revisits of the decoy delay attribute were never associated with subjects' preferences, but only the decoy amount revisits revealed the comparative advantage of choosing the target option, pushing subjects to shift their preferences towards it. This pattern is also consistent with the Król & Król (2019) results, in which only the revisits for the attribute that highlighted the inferiority of the decoy pushed subjects to prefer the target option.…”
Section: Fixation Dynamic Plot In Td Blocksupporting
confidence: 89%
“…Given that the decoy could both modify the salience of a choice alternative as a whole (e.g., focusing on the target option) and direct attention towards specific values (e.g., focusing on the attribute that makes the target superior to the decoy), a fine-grained investigation of its attentional influence on the decision-making process becomes relevant. A recent study by Król & Król (2019), one of the first using the eye-tracker methodology for decoy effects, found that subjects attention was mainly driven by the inferiority of the decoy rather than by its similarity to the target option. However, it remains to be understood whether the behavioural bias is due to an unbalanced weighting of the information as a result of its altered salience (Dimara et al, 2018) and/or to a hetero-direct attentional process (Trueblood & Dasari, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this discrepancy and the large variability between subjects in our study is that there are actually two contradicting forces in the Decoy task: on the one hand, the more similar the decoy and the target are (smaller VD), the more attention subjects would allocate to these options which would lead to a more frequent comparison between them (which would then result in a larger attraction effect) [14]. On the other hand, the more the decoy is inferior to the target (larger VD), the more the subjects would perceive the superiority of the target (larger attraction effect) [see also [56]]. In fact, both MDFT model [16] and MDbS model [14] refer to the point that when the decoy is very similar to the target and hence its inferiority is less clear, it may reduce the attraction effect.…”
Section: The Effect Of Value Distance On the Attraction Effect-heterogeneity Between Subjectsmentioning
confidence: 99%
“…The former suggested that attributes are individually processed and alternatives are repeatedly compared on the relevant value (Noguchi and Stewart 2014;Marini et al 2020). Moreover, coherently with the MDFT, which states that decoy effects take time to arise from the comparative process, it has been shown that, in a valuebased task, limiting the decision time available resulted in a reduction (or an annulment) of the attraction effect (Pettibone 2012; Marini and Paglieri 2019; see also Król and Król 2019;Marini et al 2020 for a thorough explanation of the role of the comparative process within the choice and its influence on response times). Findings on the influence of time pressure on repulsion effects are instead much scanter and less conclusive (e.g., Spektor et al 2018 observed repulsion effects regardless of response times, even though they reported some fragile influence on effect size).…”
Section: Introductionmentioning
confidence: 89%